Tomato Purple Leaf Disorder: A New Challenge for the Tomato Industry in Florida - Gary E. Vallad; Bielinski M. Santos; Jane E. Polston; David J. Schuster; Andrew W. MacRae; Jeremy D. Edwards; John W. Scott (EDIS)
PP259, a 2-page illustrated fact sheet by Gary E. Vallad, Bielinski M. Santos, Jane E. Polston, David J. Schuster, Andrew W. MacRae, Jeremy D. Edwards, and John W. Scott, describes this disorder, TPLD, observed in tomato fields in Hillsborough, Manatee, and Miami-Dade counties since 2006 — symptoms and field distribution, and the state of current research into the disorder. Published by the UF Department of Plant Pathology, November 2008.